The dimensionless differential equations describing the firmness of the basic movements of one rotor system - Філімоніхін, Геннадій Борисович; Гончаров, Валерій Володимирович; Філімоніхіна, Ірина Іванівна (Eastern-European Journal of Enterprise Technologies, 2012)
The differential equations that describe the stability of the main motions of system consisting of unbalanced rotor with a fixed point, corps and autobalancer are reduced to dimensionless form. The estimation of smallness of introduced dimensionless parameters is made; the boundaries of their changes are defined